2023
DOI: 10.1021/jacs.2c10256
|View full text |Cite
|
Sign up to set email alerts
|

Fast Surface Oxygen Release Kinetics Accelerate Nanoparticle Exsolution in Perovskite Oxides

Abstract: Exsolution is a recent advancement for fabricating oxide-supported metal nanoparticle catalysts via phase precipitation out of a host oxide. A fundamental understanding and control of the exsolution kinetics are needed to engineer exsolved nanoparticles to obtain higher catalytic activity toward clean energy and fuel conversion. Since oxygen release via oxygen vacancy formation in the host oxide is behind oxide reduction and metal exsolution, we hypothesize that the kinetics of metal exsolution should depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…38,39 Previous studies have shown that STF can exsolve metallic Fe nanoparticles upon reduction of this material. 40,41 In accordance with our hypotheses, we found that Ni irradiation can downsize the surface exsolved nanoparticles on STF to 2 nm in radius and change their compositions from unitary Fe to bimetallic Fe–Ni alloy. In addition to the surface, irradiation-induced defects also promoted bulk exsolution 14,15 in STF.…”
Section: Introductionsupporting
confidence: 90%
“…38,39 Previous studies have shown that STF can exsolve metallic Fe nanoparticles upon reduction of this material. 40,41 In accordance with our hypotheses, we found that Ni irradiation can downsize the surface exsolved nanoparticles on STF to 2 nm in radius and change their compositions from unitary Fe to bimetallic Fe–Ni alloy. In addition to the surface, irradiation-induced defects also promoted bulk exsolution 14,15 in STF.…”
Section: Introductionsupporting
confidence: 90%
“…6b shows the precipitation diagram inside the particles. 73,74 The precipitation of nanoparticles can occur through direct and indirect methods (Fig. 6c), 75 and the gradual precipitation process is closely linked to the oxygen partial pressure, which affects the rate of surface oxygen release reaction and oxygen anion diffusion in the bulk.…”
Section: Optimization Of Electrode Microstructurementioning
confidence: 99%
“…6d confirms that more oxygen release leads to more metal nanoparticles precipitation, resulting in more oxygen vacancies and creating more reaction space. 74 The nanoparticles precipitated from in situ metal can be single metal or alloy. Common transition metals used for precipitation include non-noble metals such as Fe, Co, and Ni, and noble metals such as Pd, Rh, and Ru.…”
Section: Optimization Of Electrode Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The significant enhancement in the catalytic activity of perovskites through an in situ exsolution technique has stimulated extensive studies to promote the exsolution of nanoparticles. Although the increased surface nanoparticles and oxygen vacancies significantly extend the triple phase boundaries, it should also be pointed out that the facilitated process is at the cost of consuming the host perovskite, which accelerates A-site surface segregation, formation of B-site vacancies, and even phase reconstruction of the host perovskite in the extreme case of promoting exsolution. …”
Section: Introductionmentioning
confidence: 99%